DINAMIKA EKONOMI SYARIAH DI ERA PASAR MODERN ANTARA FATWA DAN FORECAST - Soraya Ayumara; Dharma Setiawan; Amir Mukadar (UM. Bengkulu, 2025)
Indonesia's sharia economy is experiencing a transformative phase in the midst of modern market expansion, digitalization of the financial industry, and changes in Muslim consumer behavior, thus giving rise to complex dynamics between the fatwa of the National Sharia Council-Indonesian Ulema Council (DSN-MUI) as a normative instrument and market forecasts as probabilistic projections based on economic data. This article aims to analyze the interaction of these two dimensions in shaping the orientation and practice of contemporary sharia economics through a qualitative approach using the library research method on sharia economic literature, sharia maqashid, DSN-MUI fatwa documents for the 2020-2024 period, as well as sharia capital market policies and Muslim consumer behavior research. The results of the study show that the DSN-MUI fatwa performs an adaptive, responsive, and anticipatory function as a filtering mechanism and a guide to market innovation to be consistent with the sharia maqashid, with the increase in multi-contract products and the integration of Environmental, Social, Governance (ESG) values in sharia securities screening. However, the implementation of fatwas faces obstacles in the form of regulatory lag, a delay between the issuance of fatwas and industry adoption, and the risk of superficial compliance when operational practices do not reflect the substance of maslahah. Meanwhile, the Islamic capital market forecast for the 2020-2024 period projects asset growth to reach IDR 4,569.01 trillion with a focus on financial technology, waqf sukuk, and halal industry funding, but these projections tend to prioritize quantitative indicators without being integrated with the maqashid framework that assesses the distribution of benefits, justice, and sustainability. This article concludes the need for methodological integration between the istinbath fatwa process and economic forecasting tools through the development of sharia compliance indicators, continuous dialogue between scholars-economists-regulators, and strengthening maqashid literacy among industry players so that the sharia economy can play a role as a proactive normative actor that directs the modern market based on an ethical-transcendental orientation, not simply reactive to conventional market dynamics. Keywords: sharia economics, DSN-MUI fatwa, modern market, forecast, sharia maqashid